2018
DOI: 10.1002/hep.29877
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interferon Lambda 4 Genotype on Interferon‐Stimulated Gene Expression During Direct‐Acting Antiviral Therapy for Hepatitis C

Abstract: New directly acting antivirals (DAAs) provide very high cure rates in most patients infected by hepatitis C virus (HCV). However, some patient groups have been relatively harder to treat, including those with cirrhosis or infected with HCV genotype 3. In the recent BOSON trial, genotype 3, patients with cirrhosis receiving a 16‐week course of sofosbuvir and ribavirin had a sustained virological response (SVR) rate of around 50%. In patients with cirrhosis, interferon lambda 4 (IFNL4) CC genotype was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 48 publications
2
27
1
Order By: Relevance
“…Furthermore, there was a relative increase in ISG/IEG mRNA expression at TW8 and EOT relative to TW4, although levels were still lower than those observed at baseline, with the peak fold change reduction in ISG/IEG expression observed at TW4 for most ISG/IEGs (Figure , Table ). We did not observe a difference in ISG/IEG mRNA expression or fold change from baseline during treatment according to IL28B genotype in our HCV‐GT1a cohort (Figure ), in contrast to a recent report in HCV‐GT3 patients . The majority of the remaining ISG/EGs were still downregulated but again did not meet the 1.5‐fold differential expression threshold or P < 0.0007.…”
Section: Resultscontrasting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, there was a relative increase in ISG/IEG mRNA expression at TW8 and EOT relative to TW4, although levels were still lower than those observed at baseline, with the peak fold change reduction in ISG/IEG expression observed at TW4 for most ISG/IEGs (Figure , Table ). We did not observe a difference in ISG/IEG mRNA expression or fold change from baseline during treatment according to IL28B genotype in our HCV‐GT1a cohort (Figure ), in contrast to a recent report in HCV‐GT3 patients . The majority of the remaining ISG/EGs were still downregulated but again did not meet the 1.5‐fold differential expression threshold or P < 0.0007.…”
Section: Resultscontrasting
confidence: 90%
“…Therefore, direct comparison between results from the two studies is difficult, and differences in patterns of IFN‐related chemokines/cytokines may be due a combination of factors, including study design, DAA regimen, timing of mRNA/protein level evaluation, HCV genotype and the interactions between virus and host (HCV genotype and IFNL3 genotype). The latter is particularly relevant given the aforementioned study by Ramamurthy et al, where they observed dynamic changes in CXCL10 gene expression, with upregulation at treatment week 16 (end of treatment), but only in patients with the “good” responder IFNL3 genotype.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations